The quality of kindergarten care as an important element of the subjective theories [Kvalita předškolní péče jako důležitý prvek subjektivních teorií] - Maja Meško; Alenka Cemič; Mateja Videmšek; Jože Štihec; Jera Gregorc (Palacky University, 2012)
BACKGROUND: Pre-school teachers and assistants jointly manage the educational process for pre-school children in kindergartens. The selection of topics and the process orientation depends on their professionalism, which is also reflected in subjective theories influencing also their lifestyle selection. OBJECTIVE: The authors try to establish the differences in the opinions of the pre-school teachers and assistants on the quality and amount of time which children spend in kindergartens and to establish the differences in their opinions on material conditions for pursuing motor/sports activities. The aim was to establish whether the pre-school teachers apply higher standards for the evaluation of quality of leisure time spent by children and stricter criteria regarding material conditions to pursue motor/sports activities in kindergartens than their assistants. METHODS: The sample was composed of 810 pre-school teachers and assistants from the whole territory of Slovenia. The sample was not redundant. The data were collected in September 2009, within the scope of a more extensive research project titled "Professional training of education practitioners to implement elements of special pedagogical principles of the Reggio Emilia concept in the field of pre-school education from the year 2008 to 2013" and were analyzed with basic statistical parameters. The data were processed by applying the SPSS statistical programme for Windows. Every statistically significant conclusion was accepted at the risk level of 5%. RESULTS: The analysis of the results showed that the opinions of the pre-school teachers and assistants on the manner of children spending their leisure time were not statistically different. However, there were differences regarding their evaluation of the amount and quality of sports equipment and in their attitudes to motor/sports activities, in favour of pre-school teachers, who also take up motor/sports activities more often than the assistants do. We also established that more motor/sports active the pre-school teachers are during the week, the more often they participate in motor/sports activities in kindergartens, as well. CONCLUSIONS: The results of our research direct us towards providing a wider range of seminars within in-service teacher training also for the assistants and to contemplate offering recreational activities for the kindergarten staff, which shall contribute to a comprehensive bio-psycho-social status of an individual and to reshaping his lifestyle from the sedentary to the active one. [VÝCHODISKA: Na vzdělávacím procesu předškolních dětí v mateřských školách se společně podílí učitelé mateřských škol a asistenti. Výběr témat a zaměření výuky se odvíjí od jejich profesionality, které je také reflektována v subjektivních teoriích ovlivňujících volbu jejich životního stylu. CÍLE: Autoři se pokouší vymezit rozdíly v názorech předškolních učitelů a asistentů na kvalitu a množství času, které děti tráví ve školkách a vymezit rozdíly v jejich názorech na materiální podmínky k realizaci motorických/sportovních aktivit. Cílem bylo zjistit, zda předškolní učitelé uplatňují vyšší standardy, co se týče hodnocení kvality volného času, který děti tráví, a přísnější kritéria týkající se materiálních podmínek k provádění motorických/sportovních aktivit v mateřských školách než jejich asistenti. METODIKA: Výzkumný vzorek se skládal z 810 předškolních učitelů a asistentů na celém území Slovinska. Vzorek nebyl nadbytečný. Data byla sbírána v září 2009 v rámci širšího výzkumu s názvem "Profesní trénink odborníků ve vzdělávání k zavádění prvků principů speciální pedagogiky dle konceptu Reggio Emilia v oblasti předškolní výchovy v letech 2008-2013" a byla analyzována pomocí základních statistických parametrů. Data byla zpracována užitím statistického programu SPSS ve Windows. Každý statisticky významný závěr byl přijat na úrovni rizika 5%. VÝSLEDKY: Analýza výsledků ukázala, že názory předškolních učitelů a asistentů na způsob, jakým děti tráví volný čas, nebyly statisticky rozdílné. Nicméně, byly zde rozdíly týkající se hodnocení množství a kvality sportovního vybavení a rozdíly v jejich postojích k motorickým/sportovním aktivitám, a to ve prospěch předškolních učitelů, kteří navíc vykonávají motorické/sportovní aktivity častěji než asistenti. Rovněž jsme zjistili, že čím více předškolní učitelé realizují motorické/sportovní aktivity během týdne, tím častěji také realizují motorické/sportovní aktivity v mateřské škole. ZÁVĚRY: Výsledky našeho výzkumu nás vedou k tomu, abychom realizovali širší výběr seminářů v rámci profesní přípravy učitelů také pro asistenty. Zároveň také k tomu, abychom přemýšleli o poskytování rekreačních aktivit pro zaměstnance mateřských škol, které by přispěly k celkovému bio-psycho-sociálnímu postavení jednotlivce a změnily jejich životní styl ze sedavého na aktivní.]